Two natural products from the seeds of Citrus reticulata Blanco (Rutaceae) inhibit estrogen biosynthesis by regulating the PI3K-aromatase pathway - Yang, Xing; Chen, Xi; Shi, Chunqiao; Zhang, Qian; Liu, Qian; Zhou, Chunyan; Dong, Fawu; Su, Jinsong; Liu, Deming; Zhang, Yi (Frontiers in Pharmacology, 2025)
IntroductionThe seeds of Citrus reticulata Blanco (Rutaceae) (SCR), a traditional Chinese medicine derived from Citrus, is known for its diverse bioactivities, including potential anti-breast cancer effects, but the mechanism of action remains unclear.MethodsThis study aims to elucidate the active ingredients of SCR and their mechanisms of action on estrogen biosynthesis. A comprehensive phytochemical analysis, employing various chromatographic techniques, led to the isolation of 26 compounds from SCR.ResultsThe effects of these compounds on estrogen biosynthesis were evaluated in human ovarian granulosa-like KGN cells, which play a crucial role in the progression of hormone-dependent breast cancers. Network pharmacology analysis revealed that SCR may influence breast cancer development by modulating phosphorylation-related biological processes and the PI3K/AKT pathway. Among the isolated compounds, Callyspongidipeptide A (Calp) and Hesperetin 7-O-β-D-glucopyranoside (Hesp) exhibited significant inhibitory effects on estrogen biosynthesis. Calp and Hesp selectively regulated the expression of aromatase (Aro) PI.3 and P2 promoters via the PI3K/AKT pathway, inhibiting Aro mRNA and protein expression.DiscussionThese findings provide novel insights into the chemopreventive potential of SCR and support its role in the development of therapies aimed at reducing the risk of hormone-related cancers.